Kewajiban Orang Tua Memberikan Fasilitas Pendidikan Kepada Anak Disabilitas Di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang: Perspektif Hukum Nasional Dan Hukum Islam - Tara, Nurmalia; Iwan, Iwan (Faculty of Law, Andalas University, 2024)
In a legally valid marriage, parents share responsibilities for their children's rights and obligations. This becomes more challenging for parents of children with disabilities, especially in ensuring proper education. This study examines parental obligations in providing educational facilities for children with disabilities in Percut Sei Tuan sub-district, Deli Serdang district, according to Law Number 8 of 2016 concerning Persons with Disabilities and Islamic law. The research employs an empirical juridical approach with qualitative methods, emphasizing descriptive analysis and field research. It aims to align the research process with real-world facts encountered during the study. Findings reveal that some parents fulfill their obligations responsibly, implementing various strategies to support their disabled children's education. These include acting as friends and caregivers, providing transportation, creating suitable play environments, supporting home learning, and teaching social adaptation. Parents also strive to manage their emotions for stable interactions with their children. However, some parents fail to meet their obligations due to indifference towards their children's education, limited knowledge in child-rearing, and economic constraints. The study concludes that while many parents in PercutSei Tuan sub-district strive to fulfill their obligations under both national and Islamic law, challenges remain. It recommends increased support and education for parents of children with disabilities to ensure better compliance with legal and religious obligations in providing appropriate educational facilities limitations.